In Search of Remotely Piloted Aircraft Regulations State Practices and International Law Perspective What Indonesia can Learn? - Uweh, Atip Latipulhayat; Ruhaeni, Neni (Faculty of Law, Universitas Brawijaya, 2018)
Remotely Piloted Aircraft (RPA) has been used for different purposes, from hobby to military purposes. The rapid development of RPA’s technology has made RPA regulations in most countries become more quickly obsolete. It is exacerbated by the fact that there is no agreed internationally RPA regulation so far, except an amendment of Annex 2 of the Chicago Convention 1944, which broadens the notion of aircraft to include RPA. This article identifies legal issues and models of RPA regulation in several countries and what Indonesia can learn and to look for an adequate and appropriate model to make the Indonesian RPA regulation, legally acceptable and technologically adaptable. This paper argues that the Chicago Convention, the model of RPA regulations in several countries, and the special interests of Indonesia as an archipelagic state are the three important elements that should be taken into account in the establishment of an appropriate and adequate Indonesian RPA regulation. This paper used normative method whcih analysing existing legal framework in RPA